Just Folks - Guest, Edgar A. (Edgar Albert), 1881-1959 (Salt Lake City, UT : Project Gutenberg, 1997)
"Just Folks" by Edgar A. Guest is a collection of poems likely written in the early to mid-20th century. The poems reflect on everyday life, community, family, and the simple joys and sorrows of living, emphasizing friendship and appreciation for the ordinary moments that create a rich life. The verses capture a heartfelt nostalgia for simpler times, with themes of love, sacrifice, and the experiences that bind people together. The opening of "Just Folks" introduces readers to a warm and inviting perspective on the people and experiences that form a community. Through vivid imagery, Guest touches upon the beauty of a neighborly existence, the charm of small-town life, and the significance of shared memories. The collection seems to promise a variety of reflections, from the innocence of childhood to the poignant moments of adulthood, as illustrated in poems that celebrate family, friendship, and childhood joys. The tone is both whimsical and sincere, encouraging readers to find beauty in the mundane and cherish the connections that shape their lives. (This is an automatically generated summary.)
Release date is 1997-06-01
Produced by An Anonymous Volunteer, and David Widger
Keywords: American poetry